A New Method to Measure the Performance of Leveraged Exchange‐Traded Funds. Issue 4 (November 2014) - Charupat, Narat; Miu, Peter
Abstract We examine the effects of daily return compounding, financing costs, and management factors on the performance of leveraged exchange‐traded funds (LETFs) over various holding periods. We propose a new method to measure LETFs' tracking errors that allows us to disentangle these effects. Our results show that the compounding effect generally has more influence on tracking errors than other factors, especially for long holding periods and in a "sideways" market. The explicit costs (i.e., the expense ratios) and other factors (e.g., financing costs) can materially affect the performance of LETFs, especially for those with high leverage ratios and bear funds.